From Routine to Intuition: AI’s Role in Organization’s Governance and Management Decision-Making - Štrukelj, Tjaša; Gajšt, Nataša (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Nowadays, the increasing use of AI in corporate governance and management as well as business decision-making at various levels presents both opportunities and challenges. This paper integrates corporate governance and management structure, decision-making processes, and the EU AI regulatory framework. It examines how AI enters into decision-making processes in business contexts while taking into consideration ethical and legal standards. The research is based on the MER model of integral corporate governance and management, different decision-making approaches (intuitive, analytical, routine), and the AI-related EU regulatory framework (the EU AI Act). By integrating the above, this study provides a framework for responsible AI adoption in sustainable governance and management. The findings contribute to discussions on ethical use of AI in business in line with the ESG challenges in the age of AI.